THE LINGUISTIC FEATURES OF CLICKBAIT ON SOCIAL MEDIA: A STUDY CASE OF INSTAGRAM POSTS - Ali, Nurbaiti; Fitriani, Eka Surya; Losi, Rizky Vita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The rapid advancement of media, information, and technology has made all information available online. Clickbait photo posts are one area of linguistics and media study that can be conducted. The structure of clickbait photo posts needs to be examined, and information on frequently used words and phrases that relate to clickbait needs to be provided. Additionally, the significance of photo posts in social media needs to be discussed. The analysis of Instagram's clickbait photo posts was the main goal of this study. Qualitative research was used to conduct this study. The Instagram photo posts were used to collect the data. The idea of Biyani et al. (2016) regarding the categorization of clickbait was then used to their analysis. According to the statistics, clickbait was used in more than half of the 20 Instagram data points that were collected to persuade readers to click on the captions or content. From the data results, it was revealed that from twenty Instagram photo posts, it was found 2 data as exaggeration, 4 data as teasing, 3 data as inflammatory, 3 data as formatting, 1 data as bait-and-switch, and 7 data as ambiguous. Ambigious was the most category used on Instagram photo posts as a clickbait. It happens because the user tries to attract the consumer’s curiosity to buy their product. It can also make the consumer to find more description about the product to make them get valid information